IMF Survey, Volume 35, Issue 06. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
MD meets SSA leaders; ART. IV: Belgium, Ecuador, Finland, Nepal; U.K. policy frameworks; Ghana: quasi-fiscal activities; Africa and Doha Round; euro area product markets; ASI: FDI; prescriptions for financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet